Design and conduct of facility-based surveillance for severe childhood pneumonia in the Household Air Pollution Intervention Network (HAPIN) trial. Issue 1 (23rd March 2020) - Simkovich, Suzanne M.; Underhill, Lindsay J.; Kirby, Miles A.; Goodman, Dina; Crocker, Mary E.; Hossen, Shakir; McCracken, John P.; de León, Oscar; Thompson, Lisa M.; Garg, Sarada S.; Balakrishnan, Kalpana; Thangavel, Gurusamy; et al.
Pneumonia is both a treatable and preventable disease but remains a leading cause of death in children worldwide. Household air pollution caused by burning biomass fuels for cooking has been identified as a potentially preventable risk factor for pneumonia in low- and middle-income countries. We are conducting a randomised controlled trial of a clean energy intervention in 3200 households with pregnant women living in Guatemala, India, Peru and Rwanda. Here, we describe the protocol to ascertain the incidence of severe pneumonia in infants born to participants during the first year of the study period using three independent algorithms: the presence of cough or difficulty breathing and hypoxaemia (≤92% in Guatemala, India and Rwanda and ≤86% in Peru); presence of cough or difficulty breathing along with at least one World Health Organization-defined general danger sign and consolidation on chest radiography or lung ultrasound; and pneumonia confirmed to be the cause of death by verbal autopsy. Prior to the study launch, we identified health facilities in the study areas where cases of severe pneumonia would be referred. After participant enrolment, we posted staff at each of these facilities to identify children enrolled in the trial seeking care for severe pneumonia. To ensure severe pneumonia cases are not missed, we are also conducting home visits to all households and providing education on pneumonia to the mother. Severe pneumonia reduction due to mitigation of household air pollution could be a key piece of evidence that sways policymakers to invest in liquefied petroleum gas distribution programmes. We describe a facility-based surveillance strategy to determine the incidence of pneumonia in children less than 1 year of age across study settings in Guatemala, India, Peru and Rwanda http://bit.ly/31RjDQy